The organizational and regional determinants of inter-regional collaborations - Academic inventors as bridging agents - Friedrich Dornbusch; Sidonia von Proff; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2013)
Collaboration over distance is difficult to maintain in innovation projects which require a great deal of regional collaboration. However, patent documents reveal that a number of inventor teams are able to overcome long distances. Earlier literature started to investigate factors, which increase the probability of long-distance innovation co-operation. The paper at hand is restricted to patents with academic participation, but takes a close look at two types of factors in the environment of the inventors: (1) the characteristics of the university that employs the academic inventor(s), and (2) the influence of the regional environment. Research on the impact of these factors is still underdeveloped in the literature. By considering only patents with at least one academic inventor we have a relatively homogeneous subset of patents and can concentrate on the external impacts. We find that a similar research area structure, a high absorptive capacity as well as a high start-up rate foster intra-regional collaboration. More TTO staff and a larger university lead to more long-distance collaboration while the industry orientation of the university does not exert an influence on the distance between inventors.
Keywords: O31; R12; L14; 330; patents; research collaboration; academic patents; collaboration over distance; Germany